Tafsîr Khuluqun ‘Adzîm: A Methodological Studies - Saadatul Jannah (Refleksi: Jurnal Kajian Agama dan Filsafat, 2017)
Since 16th century until the recent age, study commentary is increasing gradually in Indonesia. It was characterized by the spirit of produce commentaries from scholars of Indonesia (pre-modern) such as works of Abd al-Raûf al-Sinkilî (Tarjumân al-Mustafid), Syaikh Nawawî (Tafsir Maraẖ Labid) and Aẖmad Sanusî (Tafsir al-Qurân al-Karîm), and modern era explicitly Quraish Shihab (Tafsir al-Misbah) and Didin Hafidhudddin (Tafsir al-Hijri). On the other hand, Quranic exegesis is magnetizing the modern society, academia, and the government. Two things are a sign that Indonesia necessitates developing new outlooks contained in the works of interpretation, so the view of Indonesian society are to be more extensive and varied without being limited by one of his Indonesian commentators. Yunan Yusûf , one of the Indonesian Muslim philosopher, within Tafsir Khuluqun 'Adzîm endeavors coloring Indonesian elucidation by creating distinctive work that is an interpretation of the Quran from the short chapters (Madanî) to the extended chapters (Makî). This article discovers specifically the explanation of the al-Mulk to find a methodology, sources, references and pattern of his works.  This paper depicts qualitative method with the analytical comparative approach through the two references commentaries Indonesia Tafsîr al-Azhâr and al-Miṣbah. Yunan interprets the Quran critically and decisively utilizing the color philosophy. He is able to convey the message of the Qur'an by using the correlation of the Quran (munâsabah al-Qurân bi al-Qurân) either on his work title or his clarification content. This article concludes that the better sources is preferred the more authentic the exegesis is and the more dominant the type of commentaries is the more pattern work is.